DIDACTIC POSSIBILITIES OF PEDAGOGICAL ERUDITION IN PREPARING FUTURE TEACHERS TO ORGANIZE EDUCATIONAL WORK (Universal International Scientific Journal, 2026)
This thesis analyzes the didactic possibilities of pedagogical erudition in the process of preparing future teachers for the organization of educational work. The goal is to substantiate the ways of integrating erudition into the content and methods of teaching based on a competency-based approach. The research uses methods of theoretical analysis, conceptual modeling, and didactic interpretation of pedagogical situations. The novelty is the development of structural indicators and assessment criteria of erudition in the context of educational activities.
Keywords: pedagogical erudition, educational work, didactic opportunity, competency-based approach, pedagogical situation, reflection, evaluation criteria.